Estatuto da criança e do adolescente: acolhimento familiar e o papel da comunidade - Rizzardi, Luiz Henrique (2023)
This scientific article is descriptive in nature and makes an assessment of bibliographic sources referring to the theme “family care”, whose objective is to guarantee healthy growth and good education, affective bonds and care, traits necessary for their inclusion in society. The methodology is based on research on types and reception process, in addition to data that demonstrate the historical evolution of the measure, which provides more security to the child than foster care in an institution, as it pays more attention to develop and prepare for the future. Thus, the objective is to analyze the role of the community in welcoming family for the upbringing and return of the child and/or adolescent to their biological family, if possible. In the end, through the research carried out, it was possible to conclude that foster care brings benefits not only for the children in care, as well as for the families they host. Therefore, it is necessary that all the community contributes to make this process happen.